Pendampingan Untuk Membangun Kesadaran Keuangan dan Pensiun Dini Berkelanjutan di Desa Alas Kaki Melalui Konsep FIRE - Fitria Nur Masithoh (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
This community service activity aims to enhance financial literacy and raise awareness about the importance of long-term financial planning. The program adopts the concept of Financial Independence, Retire Early (FIRE), which emphasizes planned financial management to achieve financial freedom at an early age. The results of this activity show an increase in community understanding of financial management, including budgeting, managing debt healthily, preparing emergency funds, and starting investments. Participants also began to understand the importance of early retirement planning based on the FIRE concept as an effort to achieve financial stability. Another positive impact is the collective awareness to break the cycle of risky financial behaviors, strengthen local economic capacity, and build financial independence. This community service initiative is expected to serve as a strategic first step in promoting economic sustainability in Alas Kaki Village through improved financial literacy.